Cuantificación de los servicios ambientales de secuestro de carbono en Mauritia flexuosa. En el predio estatal denominado zona de conservación … - Cabrera Mestanza, Dino (2004)
This study was carried out in order to quantify the environmental services of carbon capture of aguaje forests (Mauritia flexuosa). The location of the forests in the study is the Conservation and Ecological Recovery Zone (ZoCRE) called the "Humedal del Alto Mayo" (The Alto Mayo Wetlands) Tingana sector- Moyobamba 2013. The study consists of three main components: l. Inventory of the flora of two types of aguaje forests (dense and semi-dense) in the Alto May Wetlands ZoCRE. lnformation was collected on two plots of forest, each with an area of 2,500 m2 and in which the predominant tree species is aguaje (Mauritia flexuosa ). 300 individuals per hectare were identified in the dense aguaje plot and 122 individuals per hectare were identified in the mixed aguaje plot. Il. Determining of the biomass of the aguaje forests (dense and semi-dense). The objective was to quantify the biomass present in the dense and semi-dense aguaje forests. For this a destructive sample was made, that is, direct measurements were made of the biomass of 4 felled aguaje trees. For each of these a regression equation was generated. In both cases the height of the tree was related to the total biomass of the tree (tree measurement variables) with a good degree of significance. 111. Determining of the total carbon content of the aguaje forests (dense and semi-dense). Wlth the biomass values and the fractlons of carbon determined for each component of the dense and semi-dense aguaje forests, the amount of carbon present was obtained. This conservation area has potential as a carbon sink according to the data obtained from this study. The approximate total amount of carbon accumulated for these two types of forest in this conservation area are 41,644.56 metric tons in the semi-dense area and 67,247.016 metric tons in the dense area.